DEAD WRITE: mourning proust's signature. Issue 6 (2nd November 2018) - Dutton, James
Abstract: This article presents a reading of mourning in Marcel Proust's À la recherche du temps perdu from the philosophical perspective of Jacques Derrida to imagine a relationship between death and literature. When he writes mourning, Proust works over an irreconcilable abyss – he writes the possibility of mourning, but never writes its completion. In fact, he dies before writing any completion; he dies in deferring it, opening up a mourning for his signature that he had already begun. This, I argue, underlines the aporia that Proust contends with in writing a subjectivity of mourning and death. Death in literature dissects the arresting spectral quality of literature itself – the disability to irrevocably absent its transversal representations, or the interminable coming-back of its ghosts. In composing a literary mourning, Proust dies into a work in which the separation of signatories (Proust, any one of his narrators, us as readers, and any one of those) blurs into an indistinguishable synecdoche. As such, the article resolves upon the consideration that Proust seemingly left his novel – when we create a fictive image of death, how can we imagine anything other than life? The literary dissemination of the signature, of every past self, presents, or imagines, absence as a dream of nothingness.